Model building for current transformer paper-oil insulation state diagnostics - L.S. Skrupskaya (National Technical University "Kharkiv Polytechnic Institute", 2014)
A feedforward neural network based diagnostic model of oil-impregnated paper insulation of a current transformer has been developed. Its experimental validation as compared with a regression model has been performed.